A simulation framework for predicting process-induced distortions for precise manufacturing of aerospace thermoset composites. (1st November 2021) - Traiforos, Neoklis; Turner, Thomas; Runeberg, Patrik; Fernass, Daoud; Chronopoulos, Dimitrios; Glock, Florian; Schuhmacher, Gerd; Hartung, Daniel
Abstract: The choice of a suitable material model to simulate process induced distortions is important in order to achieve a right first time approach in the design of new moulds. This work investigates the ability of the Cure Hardening Instantaneously Linear Elastic (CHILE) model and a linear viscoelastic material model to predict process induced distortions of an aerospace composite frame. The material models were coupled with a cure kinetics model and a chemical shrinkage model in order to capture the multi-physics phenomena that take place during the curing process. The modelling of the viscoelastic behaviour of the resin is performed with the use of a generalized Maxwell model. A novel methodology is applied for shifting the relaxation times of the composite based on its temperature and degree of cure. It is shown that the viscoelastic model more accurately predicts the measured distortions due to its ability to account for stress relaxation.